The Relationship between Corporate Social Responsibility Disclosure, Profitability, and Firm Value - Ni Kadek Ari Ayuningsih; Made Gede Wirakusuma (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the relationship between Corporate Social Responsibility (CSR) disclosure and profitability with firm value. The research was conducted on companies in the oil, gas, and coal sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The independent variables in this study are corporate social responsibility disclosure and profitability, while firm size is employed as a control variable. Firm value is proxied by Price to Book Value (PBV), whereas profitability is measured using Return on Equity (ROE). This study is grounded in Stakeholder Theory and Signaling Theory to explain the relationships among the variables. The sample was determined using purposive sampling, resulting in 29 companies. The data analysis techniques applied include Pearson correlation analysis and multiple linear regression to examine both the simple relationships and the effects of corporate social responsibility disclosure and profitability on firm value. The results indicate that corporate social responsibility disclosure has a negative relationship with firm value, while profitability shows a positive and significant relationship with firm value.